The Difference in Students’ Learning Outcomes Using Problem-Based Learning and Project-Based Learning on The Concept of Vibrations and Waves - Nursahida Wahnan; Fatma Hamid; Sumarni Sahjat; Saprudin Saprudin; Taslim Buaja; Nurdin Abdul Rahman (FKIP Universitas Khairun, 2025)
This research aims to find out the differences in student learning outcomes using the problem-based learning (PBL) model and project-based learning (PjBL) model on the concept of vibrations and waves. The research type used is a quasi-experiment model, while the research design is a two-group experiment with pretests and posttests. The population of the research was class VIII students of SMP National Banau Ternate City, a total of 42 students distributed over 2 classes, with a sample of 22 students chosen with the sampling technique and then randomized to determine the experimental class and control class. Data in this research used tests. Tests were conducted before and after learning. The results of the study showed that there was a significant difference in the improvement of learning outcomes of students who participated in PBL and PjBL learning.